Podophyllotoxin Extracted from Juniperus sabina Fruit Inhibits Rat Sperm Maturation and Fertility by Promoting Epididymal Epithelial Cell Apoptosis. (4th July 2017) - Xie, Shuwu; Li, Guoting; Qu, Lijuan; Zhong, Ruihua; Chen, Ping; Lu, Zhigang; Zhou, Jieyun; Guo, Xiangjie; Li, Zhao; Ma, Aying; Qian, Yueying; Zhu, Yan
Abstract : This study aimed to investigate the antifertility effect of Juniperus sabina fruit on male rats and its possible mechanism, and hence it might be developed as a potential nonhormonal male contraceptive. Male rats were intragastrically fed for consecutive 8-week and 4-week recovery with the fruit of J. Sabina, and sperm maturation, serum testosterone level, and histopathology were analyzed. Epididymal epithelial cell culture was prepared for detection of podophyllotoxin activities. Furthermore, cell proliferation, transmission electron microscopy, Annexin V/Propidium iodide, TUNEL, RT-PCR, ELISA, and western blotting were examined. The results showed that rat sperm motility and fertility were remarkably declined after feeding the fruit. Moreover, the fruit targeted the epididymis rather than the testis. After 4-week recovery, more than half of the male rats resumed normal fertility. It was found that podophyllotoxin significantly inhibited epididymal epithelial cell proliferation, promoted cell apoptosis, and increased the mRNA and protein levels of TNF- α and the expression levels of cytochrome c, caspase-8, caspase-9, and caspase-3. Our findings suggest that the fruit of J. sabina could inhibit male rat sperm maturation and fertility. The potential mechanism might be related to podophyllotoxin, inducing epididymal epithelial cell apoptosis through TNF- α and caspase signaling pathway.